Analisis Return, Risk dan VaR Portofolio Saham JII dengan Metode SIM, MAD dan DD - Rohiman Atja; Indupurnahayu; Renea Shinta Aminda (AL-MUZARA'AH, 2022)
Before pandemic, Islamic stocks performance (ISSI, JII70, JII) contracted. During pandemic, outperformed JCI and LQ45. JII prospect is good this year, increase 5.81% early 2021, exceeded JCI (4.66%) and LQ45 (4.75%) ytd. This study uses 4 investment scenarios aimed at analyzing and exploring the Return and Risk of the selected JII Portfolio using SIM, MAD, and DD Methods; perform calculations and analyze VaR of the selected JII Portfolio; calculate and analyze the relationship between Return and Risk of the selected JII Portfolio using SIM, MAD, and DD Methods; calculate and analyze the differences in Return and Risk of the selected JII Portfolio using the SIM, MAD, and DD Methods. The research methods are SIM, MAD, DD, VaR, Correlation-Test and Difference-Test. The results of the study of the highest return of each method resulted in scenario 2, the highest risk of each method resulted in a scenario of 33.3% investment proportion, the highest VaR resulted in scenario 2. Test-correlation method in calculating returns: there is no significant relationship between the SIM-MAD and DD-MAD methods, there is a significant positive relationship between the SIM-DD method.